Settlement of embankment treated with preloading and prefabricated vertical drain (a case study) - Noormariani, Ismail (2012)
Structures built on soft soil such as clay are generally subject to excessive settlement and it may continue for a long time. It depends on the ability of the soil to dissipate excess pore pressure due to construction load. In order to construct any structure on that soft soil, soil improvement is needed. Combination of preloading and Prefabricated Vertical Drain is very effective to be use as soil improvement. This soil improvement is related to the objectives of the study which are to predict settlement of an embankment based on Terzaghi One-Dimensional Consolidation analysis. Besides that, Asoaka' s method were used to determine the actual settlement based on monitoring data and to compare the soil properties from the laboratory data with back calculated value. In this study, the predicted settlement is 1.54 meter and the actual settlement of the soil which calculated using Asoaka's Method is 0.51 meter. Back calculated value was determined in order to verify the soil properties from the laboratory. The differences between laboratory soil properties and back calculated value are been shown in the correlation form. From the analysis it shows that the correlation for the Compression Index, C lab, field = 0.40 C lab while the correlation of Recompression Index, Cr field and Coefficient of horizontal consolidation, the correlation of Coefficient of vertical consolidation, Cv field C h field = 1.02 Ch lab,. = 1.02 The correlations will be used as a reference for next project. From this case study, it shows that the ground improvement of preloading and PVD was a good agreement as it successfully reduces the time for the soil to consolidate. 0.36 Cr Cv lab,